Wage posting or wage bargaining? Evidence from the employers' side - Hanna Brenzel; Hermann Gartner; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2013)
Using a representative establishment dataset, this paper is the first to analyze the incidence of wage posting and wage bargaining in the matching pro-cess from the employer's side. We show that both modes of wage determination coexist in the German labor market, with about two-thirds of hirings being charac-terized by wage posting. Wage posting dominates in the public sector, in larger firms, in firms covered by collective agreements, and in part-time and fixed-term contracts. Job-seekers who are unemployed, out of the labor force or just finished their apprenticeship are also less likely to get a chance of negotiating. Wage bar-gaining is more likely for more-educated applicants and in jobs with special requirements as well as in tight regional labor markets. – – Dieser Aufsatz analysiert erstmals mit Hilfe einer reprä-sentativen Betriebsbefragung die Verbreitung von fixen Lohnangeboten der Arbeit-geber und von Lohnverhandlungen bei Neueinstellungen. Wir zeigen, dass sowohl individuelle Lohnverhandlungen als auch fixe Lohnangebote in Deutschland vor-kommen, wobei bei rund zwei Drittel der Neueinstellungen ein fixer Lohn angeboten wird. Besonders häufig gibt es fixe Lohnangebote im öffentlichen Dienst, in tarif-gebundenen Firmen und bei Teilzeit- oder befristeter Beschäftigung. Mit Personen, die vorher nicht erwerbstätig waren oder eine Ausbildung beendet haben, wird seltener über den Lohn verhandelt. Wahrscheinlicher ist eine Lohnverhandlung, wenn die eingestellte Person höher qualifiziert ist, wenn spezielle Qualifikationen verlangt werden oder wenn die regionale Arbeitslosigkeit gering ist.
Keywords: E24; J30; J63; M51; 330; wage posting; wage bargaining; hiring; matching; Germany